Biotic and abiotic effects on density, body size, sex ratio, and survival in immature stages of the European woodwasp, Sirex noctilio. Issue 24 (3rd November 2020) - Garnas, Jeff R.; Vann, Katie E.; Hurley, Brett P.
Abstract: Resource quality can have direct or indirect effects on female oviposition choice, offspring growth and survival, and ultimately on body size and sex ratio. We examined these patterns in Sirex noctilio Fabricus, the globally invasive European pine woodwasp, in South African Pinus patula plantations. We studied how tree position as well as natural variation in biotic and abiotic factors influenced sex‐specific density, larval size, tunnel length, male proportion, and survival across development. Twenty infested trees divided into top, middle, and bottom sections were sampled at three time points during larval development. We measured moisture content, bluestain fungal colonization, and co‐occurring insect density and counted, measured, and sexed all immature wasps. A subset of larval tunnels was measured to assess tunnel length and resource use efficiency (tunnel length as a function of immature wasp size). Wasp density increased from the bottoms to the tops of trees for both males and females. However, the largest individuals and the longest tunnels were found in bottom sections. Male bias was strong (~10:1) and likewise differed among sections, with the highest proportion in the middle and top sections. Sex ratios became more strongly male biased due to high female mortality, especially in top and middle sections. Biotic and abiotic factors such as colonization by Diplodia sapinea, weevil ( Pissodes sp.) density, and wood moisture explained modest residual variation in our primary mixed effects models (0%–22%). These findings contribute to a more comprehensive understanding of sex‐specific resource quality for S. noctilio and of how variation in key biotic and abiotic factors can influence body size, sex ratio, and survival in this economically important woodwasp. Abstract : Many insects exhibit large variation in body size and sex ratio, though specific mechanisms driving such variation are often elusive. We examined a suite of potential biotic and abiotic drivers of this variation in invasive European woodwasp ( Sirex noctilio ) across larval development stages in two South Africa pine plantations. We found that position within the tree, and to a lesser degree log moisture, Pissodes weevil densities, and Diplodia sapinea bluestain fungal colonization influenced wasp densities, growth rates, and survivial in gender‐specific ways. The trends uncovered have potentially important consequences of the ecology and management of this species.